Differentiation of Curcuma longa, Curcuma xanthorrhiza and Zingiber cassumunar by Thin Layer Chromatography Fingerprint Analysis - Mohamad Rafi; Eti Rohaeti; Ali Miftahudin; Latifah K. Darusman (Universitas Gadjah Mada, 2011)
Turmeric (Curcuma longa), java turmeric (Curcuma xanthorrhiza) and cassumunar ginger (Zingiber cassumunar) are widely used in traditional Indonesian medicine. These three herbs have relatively similar rhizomes colour so it is difficult to be differentiated especially if they are in powder form. A rapid and reliable method, thin layer chromatography (TLC) fingerprint, has been developed in order to identify, authenticate and differentiate these three herbs through fingerprint profile of chemical compounds. TLC fingerprints of the three herbs were obtained by visualization of separate zones with visible and UV (254 and 366 nm) light. The TLC fingerprint pattern is different each other and showed a specific marker zones respectively. Therefore, TLC fingerprint can be utilized for identification, authentication and differentiation method in quality control of the three herbs tested.